Dragonflies and Damselflies (Odonata) of Kadamaian, Kinabalu Park, Sabah - Choong, Chee Yen; Mahadimenakbar Mohamed Dawood (Universiti Malaysia Sabah, 2021)
The Odonata fauna of Kadamaian was surveyed from 15th to19th October, 2019 during the Borneo Geographic Expedition 2019 Kadamaian. The altitude of the survey area ranged from 400 m to 850 m above sea level, representing the lower part of Kinabalu Park. A total of 23 species in nine families were recorded – 10 species in Libellulidae, three species in Platycnemididae, two species each in Platystictidae, Calopterygidae and Coenagrionidae, and one species each in Chlorocyphidae, Devadattidae, Euphaeidae and Synthemistidae. Of these, only one species is a new record for Kinabalu Park – Pericnemis dowi. The published Odonata records were compiled to produce a species list known from Kinabalu Park. The total number of species known to Kinabalu Park is now 71. Many more parts in Kinabalu Park need to be explored for a more comprehensive Odonata fauna of the park.